2016
DOI: 10.12968/jowc.2016.25.4.184
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Ringer's solution within a dressing to elicit pain relief

Abstract: Clinical studies suggest that dressings containing Ringer's solution, such as the TenderWet and HydroClean families, provide relief from wound pain. This report reviews the available evidence and possible mechanisms for the relief of wound pain by these dressings. The ability of dressings containing Ringer's solution to provide pain relief is likely to be through providing a moist environment that is favourable for wound healing; furthermore, the dressing augments the protective barrier function by having addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…3 days, it maintains adequate wound pH, humidity, and reduce inflammation by reducing the concentration of metalloproteinases in the wound environment [ 41 ]. The dressing eliminates all known local obstacles in the healing process of chronic wounds: restores the biochemical balance in the wound bed, allows removal of the necrotic load, ensures proper moist environment within the wound, destroys the biofilm and reduces the pH value to the physiological level [ 42 ]. The use of the cleansing-absorbing dressing for a contaminated chronic wound allows lowering the level of active metalloproteins from the extracellular matrix in the wound bed, removing the residual necrotic layers, absorbing excessive amount of exudate and bringing proper therapeutic moisture into the wound.…”
Section: Cleansing-absorbing Dressingmentioning
confidence: 99%
“…3 days, it maintains adequate wound pH, humidity, and reduce inflammation by reducing the concentration of metalloproteinases in the wound environment [ 41 ]. The dressing eliminates all known local obstacles in the healing process of chronic wounds: restores the biochemical balance in the wound bed, allows removal of the necrotic load, ensures proper moist environment within the wound, destroys the biofilm and reduces the pH value to the physiological level [ 42 ]. The use of the cleansing-absorbing dressing for a contaminated chronic wound allows lowering the level of active metalloproteins from the extracellular matrix in the wound bed, removing the residual necrotic layers, absorbing excessive amount of exudate and bringing proper therapeutic moisture into the wound.…”
Section: Cleansing-absorbing Dressingmentioning
confidence: 99%
“…44 Wound dressings and their components have been shown to reduce the wound pain experienced by patients. 20,45 As well as providing a moist wound environment, which leads to reduced pain levels, the properties of the dressings themselves (for example, dressing adhesiveness) can affect the pain experienced by patients. 46 Dressings such as gauze, which can adhere to wounds, can significantly increase pain levels at dressing removal because of the adhesion of the dressing to the wound surface.…”
Section: Secondary Objectivesmentioning
confidence: 99%
“…32,88 With regards to the pain management effect of the HRWD1, this has been related to (in part) the Ringers solution component within the dressing that could effectively have a number of pathways for pain reduction. 89 A number of clinical studies have reported improvements in the levels of wound pain experienced by patients when treated with HRWD1. An open, prospective observational study of patients (n=221) with acute/chronic wounds reported that the number of patients reporting "intermediate" or "high" levels of wound pain perception decreased from 64% to 19%.…”
Section: Pain Managementmentioning
confidence: 99%